Structure of the reaction center from Rhodobacter sphaeroides R-26: membrane-protein interactions. - Yeates, T O (1987)
The energetics of membrane-protein interactions are analyzed with the three-dimensional model of the photosynthetic reaction center (RC) from Rhodobacter sphaeroides. The position of the RC in the membrane and the thickness of the membrane were obtained by minimizing the hydrophobic energy with the energy function of Eisenberg and McLachlan. The 2-fold symmetry axis that relates the L and M subunits is, within the accuracy of 5 degrees, parallel to the normal of the membrane. The thickness of the membrane is estimated to be 40-45 A. Residues that are exposed to the membrane are relatively poorly conserved in the sequences of homologous RC proteins. The surface area of the RC is comparable to the surface areas of water-soluble proteins of similar molecular weight. The volumes of interior atoms in the RC are also similar to those of water-soluble proteins, indicating the same compact packing for both types of proteins. The electrostatic potential of the cofactors was calculated. The results show an asymmetry in the potential between the two possible pathways of electron transfer, with the A branch being preferred electrostatically.